An Assessment of Public Sector Accounting in Kano State: Issues, Challenges and Way Forward - Sunusi, Mansur (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study examines the assessment of public sector accounting in Kano State, highlighting the key issues, challenges, and potential solutions for improving its effectiveness. This study identifies persistent problems, including an inadequate financial management system, a lack of skilled personnel, delays in financial reporting, and weak enforcement of regulations. A descriptive survey research design was adopted to source data using a structured questionnaire. The target population of the study is made up of fifty (50) respondents, which include public sector accountants, financial officers, and auditors. The self-developed questionnaire using a 4-point Likert scale was used. The instrument was validated by two experts. The reliability coefficient of 0.81 was obtained. Fifty questionnaires were developed and administered, out of which 44 were filed and returned, which makes 88%. It was concluded that inadequate financial reporting and a lack of skilled personnel are the key issues of the Kano state public sector. The study recommends, among others, that the state government should adopt and implement International Public Sector Accounting Standards (IPSAS), moving from cash to accrual-based accounting. This ensures a more comprehensive and transparent representation of the state’s financial position.
Keywords: Public Sector Accounting; Transparency; Accountability Assessment; Financial Management